Perinatal mortality risk factors in dairy calves. (November 2019) - Cuttance, Emma; Laven, Richard
Highlights: Perinatal mortality is defined as death of a full term calf either during parturition or shortly after (up to 48 h). Major risk factors for perinatal mortality are calf sex (male), primiparous dams, assistance at calving, and twin calves. Assessing the generalisability of many papers is challenging without data on how the risk factors affect population risk. Abstract: Dairy calf mortality is an area of interest worldwide as animal welfare continues to increase in importance to the consumer. Perinatal mortality, defined as death of a full term calf either during parturition or shortly after (up to 48 h), is a major component of overall calf mortality with estimates of losses in large scale multi-farm studies suggesting that 2.4–9.7% of calves are lost across a wide range of different systems. In order to reduce perinatal mortality, we need to understand the key risk factors which influence its prevalence. This review explores the literature on risk factors associated with perinatal mortality, with a particular focus on the limitations of the published literature, applicability of the data, and the challenges faced when trying to compare data across studies. Overall, calves that are male, born to primiparous dams, are twins or had to be assisted during the calving process, are at a higher risk of mortality.